SIKAP MASYARAKAT DAN KONSERVASI KASUS STIMULUS PAKIS SAYUR DI DESA GUNUNG BUNDER II, KECAMATAN PAMIJAHAN, BOGOR - Zakiyyah Zakiyyah; Ervizal A.M. Zuhud; Sumardjo Sumardjo (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2016)
Vegetable ferns (Diplazium esculentum (Retz) Sw) which grows in the forest directly utilized by community and often does not take into account the survival. Utilization of vegetables ferns should be in line with its preservation is to do conservation actions that are based on sustainable development in line with the Regulation of Law No. 5 In 1990 , concerning the conservation of natural resources. To support the law, community’s attitudes must be constituted in accordance with the concept of "tri-stimulus amar proconservation" which consists of the natural, benefits, and willingly stimulus. This research aims to determine how the community’s attitude toward conservation of vegetable fern. Data taken from survey results with a questionnaire of attitudes processed with aid MSI (Methods of Successive Interval) to see percentage numbers of community’s attitude. Based on the results of survey on 25 respondents, community’s attitudes indicate a positive attitude supporting the conservation vegetables fern but not entirely impact on the willingly stimulus. Community had no willingness to plant vegetable ferns because of the availability are abundant, does not have the land to grow and the lack of skills on how to plant vegetables ferns.